Sequencing, de novo assembly and comparative analysis of Raphanus sativus transcriptome - Wu, Gang; Zhang, Libin; Yin, Yongtai; Wu, Jiangsheng; Yu, Longjiang; Zhou, Yanhong; Li, Maoteng (Frontiers in Plant Science, 2015)
Raphanus sativus is an important Brassicaceae plant and also an edible vegetable with great economic value. However, currently there is not enough transcriptome information of R. sativus tissues, which impedes further functional genomics research on R. sativus. In this study, RNA-seq technology was employed to characterize the transcriptome of leaf tissues. Approximately 70 million clean pair-end reads were obtained and used for de novo assembly by Trinity program, which generated 68,086 unigenes with an average length of 576 bp. All the unigenes were annotated against GO and KEGG databases. In the meanwhile, we merged leaf sequencing data with existing root sequencing data and obtained better de novo assembly of R.sativus using Oases program. Accordingly, potential simple sequence repeats (SSRs), transcription factors (TFs) and enzyme codes were identified in R.sativus. Additionally, we detected a total of 3,563 significantly differentially expressed genes (DEGs, P≤0.05) and tissue-specific biological processes between leaf and root tissues. Furthermore, a TFs-based regulation network was constructed using Cytoscape software. Taken together, these results not only provide a comprehensive genomic resource of R. sativus but also shed light on functional genomic and proteomic research on R. sativus in the future.